Budidaya Udang Vaname pada Berbagai Skala Produksi (Studi Literatur) - Yustiati, Ayi; Kanna, Iskandar (Jurnal Perikanan Unram, 2025)
Vaname shrimp (Litopenaeus vannamei) cultivation is growing rapidly in Indonesia and has various production scales, from traditional to super-intensive. This study examines the technical and economic differences of each production scale based on literature studies. Technically, the traditional scale still relies on natural environmental conditions with a stocking density of 5–9 shrimp/m2 and a productivity of 0.1–0.5 tons/ha/period. The traditional-plus scale is a development of the traditional scale with several improvements in technical aspects such as pond bottom soil processing, additional feeding, and simple water quality management with a stocking density of 10–49 shrimp/m2 and a productivity of 0.7–1.5 tons/ha/period. The semi-intensive scale begins to implement better aeration and water quality management, increasing the stocking density to 50–79 shrimp/m2 with a productivity of 4–8 tons/ha/period. At intensive and super-intensive scales, the use of technologies such as biofloc systems, Recirculating Aquaculture Systems (RAS), and Internet of Things (IoT) allows for higher stocking densities (80-150 shrimp/m2 and 250-400 shrimp/m2) with productivity reaching 15-20 tons/ha/period and 100-150 tons/ha/period. Economically, a more intensive production scale shows greater benefits. The traditional scale has an Internal Rate of Return (IRR) of 10-20% with a payback period of 3-5 years, while the semi-intensive and intensive scales have an IRR of 20-50% with a shorter payback period (1.5-3 years). The super-intensive scale offers the highest benefits with an IRR> 50%, a Net Present Value (NPV) of billions of rupiah, and a payback period of less than 1.5 years. However, intensive and super-intensive scales require large initial capital and more complex management systems, especially in terms of water quality and biosecurity. The results of this study indicate that increasing the scale of production can increase efficiency and profits, but also carries higher risks. Therefore, the selection of production scales must consider technical readiness, financial resources, and good risk management. The application of technologies such as biofloc, RAS, and IoT has the potential to increase the efficiency and sustainability of whiteleg shrimp cultivation. Support from the government and stakeholders is needed to increase the competitiveness of the aquaculture industry through policies that support innovation and sustainability.